Issues and future trends in teaching physical education: a preliminary study - Kiat, L. B. (Institute of Electrical and Electronics Engineers Inc., 2016)
This study discusses the issues and future trends of teaching physical education subject. The data is elicited from an interview conducted with four expert teachers. Four issues were identified after conducting an analysis of the interview transcript. The issues are time, teaching method, perception toward physical education and future trends in teaching and learning physical education. Physical education is important for a child's development from the cognitive, social and physical health aspect. Physical education is not emphasized in school. Based on the data obtained, a new teaching method must be devised to prevent the lack of interest in learning physical education in the classroom.